Pengaruh Model Pembelajaran Realistic Mathematics Education Berbasis Etnomatematika terhadap Literasi Numerasi Siswa Sekolah Dasar - Adini Nur Abidah; Anwar Ardani (AR-RIAYAH: Jurnal Pendidikan Dasar, 2024)
The use of teacher-centred learning models and the lack of media utilisation in the mathematics learning process contribute to the low numeracy literacy skills of students. This study aims to determine the effect of the Ethnomathematics-based Realistic Mathematics Education learning model on students' numeracy literacy. This type of research is quantitative research with Quasi Experiment method with Non Equaivalent Posttest Only Group Design. The population in this study was elementary schools in Kaliwadas Village and the samples in this study were class V of Kaliwadas 01 Elementary School as the experimental group and class V of Kaliwadas 03 Elementary School as the control group. The data collection technique used test, observation, and documentation. Data analysis technique used regression test and independent t-test. The result showed that Fcount was 65.89 and Ftable was 4.225 so Fcount > Ftable. From the results of the independent t test, it shows that the tcount is 7.2216 and the ttable is 2.01537 so that the tcount> ttable.  It can be said that learning with the ethnomathematics-based RME model affects students' numeracy literacy.